Health Beneficial Properties of Grapevine Seed Extract and Its Influence on Selected Biochemical Markers in the Blood, Liver and Kidneys of Rattus norvegicus - Sochorova, Lenka; Baron, Mojmir; Dadakova, Katerina; Kasparovsky, Tomas; Sochor, Jiri (Molecules, 2021)
Cadmium (Cd) is a heavy metal that occurs in all areas of the environment, including the food chain. In the body, it causes oxidative stress by producing free radicals that are harmful to the cells. Grape seed extract (GSE) contains a wide range of biologically active components that help to neutralize the adverse effects of free radicals. In this study, the effects of GSE prepared form semi-resistant grapevine cultivar Cerason, which is rich in phenolics, on biochemical markers of brown rats exposed to the effects of cadmium were monitored. GSE increased the plasma antioxidant activity and, in the kidneys and the liver, Cd content was significantly lowered by GSE co-administration. Accordingly, the increase in creatinine content and alanine aminotransferase activity and the decrease of catalase and superoxide dismutase activities caused by cadmium were slowed down by GSE co-administration. The results of this work reveal that grape seed extract offers a protective effect against the intake of heavy metals into the organism.
Keywords: Cadmium; Animals; biologické markery; kreatinin; fytonutrienty; Grape Seed Extract; semena rostlinná; Aspartate Aminotransferases; Alanine Transaminase; kadmium; Rats, Wistar; extrakt ze semen vinné révy; Health; antioxidancia; Phytochemicals; Antioxidants; močovina; ledviny; Metallothionein; játra; superoxiddismutasa; Catalase; Liver; zvířata; aspartátaminotransferasy; Kidney; zdraví; Seeds; Urea; katalasa; metalothionein; Creatinine; potkani Wistar; Superoxide Dismutase; Biomarkers; alanintransaminasa